2014
DOI: 10.1007/s11999-014-3745-0
|View full text |Cite
|
Sign up to set email alerts
|

Is Unilateral Kyphoplasty as Effective and Safe as Bilateral Kyphoplasties for Osteoporotic Vertebral Compression Fractures? A Meta-analysis

Abstract: Unilateral and bilateral percutaneous kyphoplasties appear to be safe and effective for treating osteoporotic vertebral compression fractures. No clinically important differences were found between them. Considering less operation time and less cost, we suggest that a unilateral percutaneous kyphoplasty is advantageous, but because of the poor quality of the evidence, high-quality randomized controlled trials are required to resolve this issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 35 publications
1
35
0
Order By: Relevance
“…Another important controversy is the comparison between the use of 1 or 2 portals in vertebral augmentation treatments. 5,16,19 Although this controversy is mainly focused on kyphoplasty, in our study we did not find any significant differences between the use of 1 or 2 portals in either vertebroplasty or kyphoplasty, which coincides with multiple previously conducted studies. 5,16,19 Therefore, from our point of view, a decision will depend on the surgeon's experience, as well as on the situation and the quantity of fractures to be treated.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Another important controversy is the comparison between the use of 1 or 2 portals in vertebral augmentation treatments. 5,16,19 Although this controversy is mainly focused on kyphoplasty, in our study we did not find any significant differences between the use of 1 or 2 portals in either vertebroplasty or kyphoplasty, which coincides with multiple previously conducted studies. 5,16,19 Therefore, from our point of view, a decision will depend on the surgeon's experience, as well as on the situation and the quantity of fractures to be treated.…”
Section: Discussionsupporting
confidence: 91%
“…6,13,15,16,18 Another controversy revolves around comparing the effectiveness of and complications resulting from the use of one versus two portals. 5,6,16,19 For this reason, the objective of this study is to compare the results obtained and the incidence of complications from these two procedures in patients treated in our facility.…”
Section: Introductionmentioning
confidence: 99%
“…The bilateral approach, which is relatively safe and effective, is considered the mainstay of PKP for Kummell disease (8,9). Certain studies have proposed that, as compared with bilateral PKP, unilateral PKP may offer a number of benefits, including a shorter operative time, lower complication rate and less radiation exposure (10,11). A comparison of bilateral and unilateral approaches may provide evidence for surgeons in the selection of PKP.…”
Section: Introductionmentioning
confidence: 99%
“…Operation time and volume of cement were significantly lower in the unipedicular kyphoplasty group. 58 More recently, Huang et al 59 published a meta-analysis of 5 low quality RCT. The authors also found no differences between the two approaches, in regard to clinical outcomes, complications such as cement leakage and adjacent vertebral fractures, kyphosis angle reduction, or anterior vertebral height restoration.…”
Section: Bilateral Versus Unilateral Approachmentioning
confidence: 99%